Mitophagy in hypertension-mediated organ damage - Ma, Yulong; Zhou, Xunjie; Gui, Mingtai; Yao, Lei; Li, Jianhua; Chen, Xiaozhe; Wang, Mingzhu; Lu, Bo; Fu, Deyu (Frontiers in Cardiovascular Medicine, 2024)
Hypertension constitutes a pervasive chronic ailment on a global scale, frequently inflicting damage upon vital organs, such as the heart, blood vessels, kidneys, brain, and others. And this is a complex clinical dilemma that requires immediate attention. The mitochondria assume a crucial function in the generation of energy, and it is of utmost importance to eliminate any malfunctioning or surplus mitochondria to uphold intracellular homeostasis. Mitophagy is considered a classic example of selective autophagy, an important component of mitochondrial quality control, and is closely associated with many physiological and pathological processes. The ubiquitin-dependent pathway, facilitated by PINK1/Parkin, along with the ubiquitin-independent pathway, orchestrated by receptor proteins such as BNIP3, NIX, and FUNDC1, represent the extensively investigated mechanisms underlying mitophagy. In recent years, research has increasingly shown that mitophagy plays an important role in organ damage associated with hypertension. Exploring the molecular mechanisms of mitophagy in hypertension-mediated organ damage could represent a critical avenue for future research in the development of innovative therapeutic modalities. Therefore, this article provides a comprehensive review of the impact of mitophagy on organ damage due to hypertension.